Regional income differentials and the issue of regional equalisation in Ireland - Boyle, G. E.; McCarthy, Thomas G.; Walsh, Jim (Statistical and Social Inquiry Society of Ireland, 1999)
The policy perspective we will argue for in this paper has three broad aspects. First, we will argue that policies of redistribution that have an explicit regional emphasis are unlikely to be justified in Ireland's unitary State. Second, we will stress the importance of agglomeration economies in sustaining regional productivity imbalances at least in the 1990s. Third, we will argue that there is a key role for State investment strategies and user-cost pricing schemes which concentrate on expanding the commuting compass of those existing centres of concentration that have sufficient critical mass to generate and re-generate agglomeration economies. - [Extract p.3]
Read before the Society, 15 April 1999
Keywords: Regional development - Ireland; 314.15